2016
DOI: 10.1099/ijsem.0.001273
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiopsis sediminis sp. nov., isolated from mangrove sediment

Abstract: A filamentous actinomycete, designated strain 1SS5-02T, was isolated from mangrove sediment collected from Ranong province, Thailand. The strain formed aerial and substrate mycelia composed of long, branched hyphae. Aerial mycelia differentiated into non-motile, rod-shaped spores. The organism contained meso-diaminopimelic acid and no diagnostic sugars in whole-cell hydrolysates. The predominant menaquinones were MK-11(H4), MK-11(H6) and MK-11(H8). Polar lipids comprised phosphatidylcholine, phosphatidylethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Basonym: V errucosispora sediminis Dai et al 2010 (The name Micromonospora sediminis has already been validly published (Muangham et al, 2016 ), hence a new epithet has been chosen to avoid homonyms).…”
Section: Discussionmentioning
confidence: 99%
“…Basonym: V errucosispora sediminis Dai et al 2010 (The name Micromonospora sediminis has already been validly published (Muangham et al, 2016 ), hence a new epithet has been chosen to avoid homonyms).…”
Section: Discussionmentioning
confidence: 99%
“…Members of this genus are widely distributed in hypersaline environments and produce very distinct secondary metabolites ( Tsujibo et al, 2003 ; Sun et al, 2015 , 2017 ; Sharma and Singh, 2016 ). In past few years, attempts to isolate novel Nocardiopsis strains were made and many novel species such as N. algeriensis ( Bouras et al, 2015 ), N. mangrovei ( Huang et al, 2015 ), N. oceani and N. nanhaiensis ( Pan et al, 2015 ), N. ansamitocini ( Zhang et al, 2016b ), N. sediminis ( Muangham et al, 2016 ), N. rhizosphaerae ( Zhang et al, 2016c ), and N. akesuensis ( Gao et al, 2016 ) have been reported. At present, the genus comprises 53 species and 5 subspecies ( 1 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The members of the genus Nocardiopsis were widely distributed in the environment, mainly in soil, especially alkaline soil [3], desert [4, 5] and high-salinity soil [6, 7]. This genus encompasses distinct features from other genera, such as well-developed substrate mycelium that fragments into non-motile bacillary and coccoid elements [8] and aerial hyphae that differentiates into smooth surfaced spores; whole cell hydrolysates contain meso -diaminopimelic acid but lack diagnostic sugars [9]; the major menaquinones comprise variably hydrogenated menaquinones with ten isoprene units [10]; the predominant polar lipids include phosphatidylethanolamine and phosphatidylglycerol [11]. Species of the genus Nocardiopsis were characterized chemotaxonomically and physiologically in their taxonomy, and distinguished between Nocardiopsis species by differences in cell wall composition and menaquinone, phospholipid, and fatty acid patterns [12].…”
Section: Full-textmentioning
confidence: 99%